Estimation of mixing in the troposphere from Lagrangian trace gas reconstructions during long-range pollution plume transport - Pisso, Ignacio; Real, Elsa; Law, Kathy S.; Legras, B.; Bousserez, N.; Attié, Jean-Luc; Schlager, H. (Journal of Geophysical Research, 2009)
International audience The dispersion and mixing of pollutant plumes during long-range transport across the North Atlantic is studied using ensembles of diffusive backward trajectories in order to estimate turbulent diffusivity coefficients in the free troposphere under stratified flow conditions. Values of the order of 0.3-1 m2 s−1 and 1 × 104 m2 s−1 for the vertical and horizontal diffusivity coefficients D v and D h , respectively, are derived. Uncertainties related to the method are discussed, and results are compared with previous estimates of atmospheric mixing rates. These diffusivity estimates also yield an estimate of the vertical/horizontal aspect ratio of tracer structures in the troposphere. Results from this case study are used to estimate grid resolutions needed to accurately simulate the intercontinental transport of pollutants as being of the order of 500 m in the vertical and at least 40 km in the horizontal. This work forms the basis of high-resolution chemical simulations using ensembles of diffusive backward trajectories.